Xanthium strumarium L. Extracts Produce DNA Damage Mediated by Cytotoxicity in In Vitro Assays but Does Not Induce Micronucleus in Mice. (14th June 2014) - Piloto Ferrer, Janet; Cozzi, Renata; Cornetta, Tommaso; Stano, Pasquale; Fiore, Mario; Degrassi, Francesca; De Salvia, Rosella; Remigio, Antonia; Francisco, Marbelis; Quiñones, Olga; Valdivia, Dayana; González, Maria L.; et al.
Abstract : Xanthium strumarium L. is a member of the Asteraceae commonly used in Cuba, mainly as diuretic. Some toxic properties of this plant have also been reported and, to date, very little is known about its genotoxic properties. The present work aims was to evaluate the potential cytotoxic and genotoxic risk of whole extract from Xanthium strumarium L. whole extract of aerial parts. No positive response was observed in a battery of four Salmonella typhimurium strains, when exposed to concentrations up to 5 mg/plate, with and without mammalian metabolic activation (liver microsomal S9 fraction from Wistar rats). In CHO cells, high concentrations (25–100  μ g/mL) revealed significant reduction in cell viability. Results from sister chromatid exchanges, chromosome aberrations, and comet assay showed that X. strumarium extract is genotoxic at the highest concentration used, when clear cytotoxic effects were also observed. On the contrary, no increase in micronuclei frequency in bone marrow cells was observed when the extract was orally administered to mice (100, 500, and 2000 mg/Kg doses). The data presented here constitute the most complete study on the genotoxic potential of X. strumarium L. and show that the extract can induce in vitro DNA damage at cytotoxic concentrations.